ANALISIS PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS (STUDI PADA PERUSAHAAN MANUFAKTUR SUB FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020) - Habiburrahman, Nawal; Sudarsono, Bambang (Eco-Entrepreneur, 2023)
Nawal Habiburrahman. Analysis of the Effect of Leverage and Liquidity on Financial Distress in Manufacturing Companies of the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange in 2016 - 2020. Supervised by Drs. Bambang Sudarsono, MM. This study aims to determine the effect of Leverage and Liquidity variables on financial distress in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2020. The approach used in this research is quantitative research. The number of samples in this study were 18 companies. The data analysis technique used in this research is multiple linear regression analysis, with hypothesis testing t statistical test and f statistical test. Based on the research that has been done, the results show that leverage has a significant negative effect on financial difficulties, while liquidity has a non-significant positive effect on financial difficulties, but leverage and liquidity have a positive and significant effect simultaneously on financial difficulties.